Leadership style and employee performance: The mediating role of training - Abdul Rahman (Journal of Management and Business Insight, 2025)
Purpose-Improving employee performance cannot be separated from how companies manage leadership styles and can organize relevant training programs. This research examines how leadership styles influence employee performance, with training as a mediating factor at the Yogyakarta City Transportation Agency in Indonesia. Design/Methodology/Approach-Convenience sampling was employed as the sampling strategy. The sample consisted of 75 employees, and data were collected via questionnaires distributed physically and completed directly by employees at the Yogyakarta City Transportation Agency. Following data collection from the respondents, Smart PLS was employed to arrange the information in tables and conduct the analysis. Findings-The findings demonstrated that while training had no discernible impact on employee performance, either directly or through mediating the relationship between leadership style and performance, leadership style had a significant and positive direct effect on employee performance. Research limitations/implications-The study's limitations are due to the small sample size and the fact that it only looked at Yogyakarta City Transportation Agency employees. Therefore, considering the unique characteristics of each employee in their respective agencies, the results of this study might not necessarily apply to other similar companies. Originality/value-This study is original because it focuses on the Yogyakarta City Transportation Agency, an agency that has distinctive field work and community service characteristics that differentiate it from other organizations. This research is important because it enhances the knowledge base related to managing people in government jobs. Furthermore, it offers hands-on advice on how to boost the skills of leaders and make training more impactful, ultimately helping workers do their jobs better.